Economic aspects of applying hail protection nets in apple plantations - Apáti, F.; Soltész, M. (International Journal of Horticultural Science, 2011)
The up to date intense apple growing in Hungary is capable to produce yearly about 500-1000 thousand Ft/ha income, which means that the investment of 4 000–5 000 thousand Ft is returned by producing 10-20% net income. The economic balance may, however, be upset by the damage caused by hail, quantitative and qualitative, with an apparently increasing frequency experienced in each third or fourth year. Estimates prove that each hail causing 50% damage may reduces the income proportionately to the capital by 1.5–2.0 percent points, which means a serious threat for the economy of apple production. According to calculations, a plantation producing 30–40 t/ha yields would not be able to raise incomes compensating the investment of 7.0–10.0 million Ft/ha, let alone the frequencies of hail damages. Consequently, 50–60 t/ha yields are needed to become successful, and in planning of new plantations those high yields are aimed with hail nets. An additional difficulty is represented by a lack of financial resources to install hail protection nets.